Islamic Multicultural Da’wa towards Qur’anic Community by Nusantara Islam Style - Yesin, Nur (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Islamic da’wa must continue and be strengthened. Da’wa cannot stop before there is a command to stop da’wa. But this preaching should not be the legitimacy and motivation to behave as he pleases without censorship. Da’wa cannot be separated from the spirit of preaching. Such as Islamic da’wa. It has a clear foundation. He leaned on the spirit of the da’wa of the polite predecessor, full of encouraging invitations. The polite da’wa, one of which gave birth to Nusantara Islam. The light grace of God. He became a distinctive variant that is very typical. Friendly and peaceful Islam. The Da’wa is now passed on by Nusantara Islam as its heir. Da’wa that is thick with the spirit of da’wa, upholds the great values of al-akhlaq al-karimah to realize the Islamic community of Qur’ani.